Prevalence of asthma and other allergic conditions in adults in Khuzestan, southwest Iran, 2018 - Esmaeil Idani; Hanieh Raji; Farzan Madadizadeh; Bahman Cheraghian; Maryam Haddadzadeh Shoshtari; Maryam Dastoorpoor (BMC, 2019)
Abstract Background Health information on the dimensions of asthma and allergic conditions in Khuzestan Province, as a major industrial and polluted area in Iran as and the Middle East, is inadequate. This study was performed to measure the prevalence of asthma and other allergic conditions in adults in Khuzestan Province. Methods This population-based cross-sectional study was carried out in 17 villages and 27 cities of Khuzestan Province during the years 2017-2018 on 20 to 65 year old respondents. Two-stage cluster sampling was used. The ECRHS (European Community Respiratory Health Survey) questionnaire was completed for individuals with additional questions regarding other allergic conditions. Results In the study, 5720 questionnaires were distributed of which 5708 were returned. The prevalence of current asthma was 8.5% and that of asthma-like symptoms was 19.0%. The most common symptoms of asthma were nocturnal cough (13.6%), chest tightness (12.3%) and wheezing (13.1%). The prevalence of allergic rhinitis (AR), eczema and airway hyperresponsiveness were 27.2, 10.7, and 38.7%, respectively. The prevalence of current asthma was strongly correlated with age, current location (city, village), and the smoking status of respondents (p < 0.05). Conclusion The prevalence of current asthma and asthma-like symptoms in Khuzestan Province is almost twice as high as in Iran. Given the high prevalence of symptoms of airway hyperresponsiveness in the entire province, it is necessary to take environmental measures to mitigate the emergence of new cases of asthma among the residents. In addition, surveillance studies are necessary to monitor the trends in the prevalence of asthma in this province.